Assess the Opinions of Nurses in Hospitals in the Al-Diwaniah Governorate on the Most Common Drug Errors and the Factors that Lead to Them - Kareem, Haidar Jabbar; Fareed, Wasen Abdul‑Ameer Ali; Hamed, Dhyaa Shinyar (Newinera Publisher, 2024)
This study aims to investigate nurses' perspectives on medication errors and the factors that lead to them. A total of 355 nurses from three general hospitals and a private facility in Aldiwaniah City participated in this descriptive cross-sectional research. We created a five-part self-administered questionnaire based on previously published research and gave it to the nurses throughout their shifts. We contacted 355 nurses, and 352 of them completed the questionnaire. The data analysis employed descriptive statistics. According to the study's results, giving medication at the wrong time was the most common type of medication mistake, scoring 2.5±1.02. Errors with a lower severity were less common. 64% of nurses did not report prescription mistakes, but 44.6 percent did so orally, and 56.8% did so in the form of an event report. The most frequent obstacle to reporting was a misunderstanding of what defines a drug error, indicating a substantial discrepancy between their perception and knowledge. Common medication errors (MEs) that nurses describe include administering medication to the incorrect patient at the wrong time, delivering IV medication at the incorrect speed, and forgetting to add a dosage. Both environmental factors (frequent visits) and personal factors (stress and fatigue) contribute to these errors. There is a statistically significant correlation between the incorrect time and characteristics such as ward, hospital type, age, gender, and educational attainment. There is a strong correlation between systemic problems and incorrect time errors.